Un sistema Web-GIS dei Beni di Interesse Culturale e Paesaggistico nelle Marche - Conforti, Annalisa; D'Amico, Luigi Federico; Issini, Giovanni; Malinverni, Eva Savina; Tassi, Camilla; Trotta, Sara (Archeomatica, 2021)
The Italian Ministry of Culture regional branch in the Marche region is developing a Web-GIS system dedicated to the local cultural heritage focused on architectural and landscape sites. The informative system is based on two main datasets: the regional listed architectural heritage sites and the architectural heritage sites affected by 2016 earthquake events. The data processing and the following datasets merging arose challenging issues linked to the complexity of the information associated with each architectural site. Through a research partnership, the project team firstly defined a method based on the critical understanding of the cultural features of the sites. Subsequently, the data processing procedure was codified through a mismatch control protocol, tested over a sample of the sites.